Implementation of the Indonesian Banking Architecture as a Blueprint of the Direction And Order of the National Banking System: Empirical Study of Indonesian Commercial Banking - Puspitasari, Devy M.; Setiadi, Nugroho J.; Rizkiyanti, Nurrina (Bina Nusantara University, 2015)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), earning assets, and liquidity against Return on Asset (ROA) in the conventional bank which has the biggest asset listed in Indonesian Stock Exchange (IDX) during the period of 2006 to 2010. This research used time series data from Bank Indonesia’s report and financial reports annually published by banking firms listed in IDX. After passing the purposive sampling, there were 27 conventional banks listed in IDX as sample in this study. By using multiple regression analysis (F-test), results showed that CAR, Non Performing Loan (NPL), and Non Performing Loan (NPL) collectively have significant influence on ROA. However, by using individual analysis (t-test), NPL has a negative and significant influence on ROA, while CAR and LDR have no significant influence on ROA.